Measurement the Chemical Composition and Topography of Copper Nickel Titanium Arch Wires at Dry and Wet conditions (An In-Vitro Study) - Saba Ammar Mohammed1 , Abeer Basim Mahmood2 , Mohammed Nahidh2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The characteristics surface, such as, topography, and rigidity of orthodontic arch wires areessential determining factor of the effectiveness,of arch wire-guided tooth movement. They also affect,in the potential of corrosion,and the aesthetics,of orthodontic components. This study was considered toevaluate the chemical composition and topography of Cu-NiTi arch wires from different companies in,dryand,wet condition( acidic and,neutral artificial saliva). Materials and methods Three,types of CuNiTiorthodontic,archwires from,different brands were,used: CuNiTi (Ormco brand),, CuNiTi (IOS brand)and,CuNiTi (Orthotechnology brand).,They were rectangular,(0.018*0.025 inch) in cross,section and cutinto pieces,of 20 mm in length.,30 pieces,from each,company were separated into 3 groups; one group wasleft dry condition,and other,2 groups, ten pieces,for each group were submerged in,artificial saliva,(pH=6.75± 0.015) and,(pH=3.5 ± 0.015) at 37ºC ,for 2 months. The SEM and EDS was used to assess surface analysisof wholly samples.,Results: After soaking period, CuNiTi wires from orthotechnology brand,exhibited thehighest change in chemical composition and topography among the study groups. Instead, the least changein chemical composition and topography surfaces were CuNiTi wires from Ormco brand,when comparedto,analogous arch wires. Conclusion: The CuNiTi arch wires from Ormco brand were the greatest and themost appropriate alignment in orthodontic archwires in term of the least changes in surface of Cu-NiTiinitially and during the course of this study period.